Effizienzgewinn durch Regionalisierung? Abgrenzung homogener Politikaktionsräume in Flusseinzugsgebieten - Huchtemann, Dirk (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Diffuse deposits of fertilizers and nutrients caused by agriculture constitute a main problem for the maintenance of surface water bodies. A reduction of these deposits cannot be achieved by means of technical solutions, but only through a change in agricultural practice in a river catchment area. To stimulate and support such a change in behaviour should be the aim of a regionally adapted river area management. In order to minimize the costs that would be caused by the organization of such a river area management, a methodical approach is developed in this work which distributes the competences for political influence efficiently in a river catchment area. Efficiency means in this context that measures for the control of diffuse pollution can be implemented with a possibly low sum of transaction and production costs. This methodical approach is applied in the catchment area of the river Ems. In this area homogeneous groups of neighbouring municipalities are created with the aid of a geographic information system in which measures for the control or the reduction of diffuse nutrient deposits could be carried out more efficiently than is possible within the counties in which the municipalities are presently united.